Political metaphors in the speech of parliamentary leaders - Tarasheva, Elena (Yearbook of the Department of Foreign Languages and Cultures, 2024)
The study traces conceptual metaphors in political speeches in Bulgarian. The corpus for the study comprises the parliamentary speeches given by the leaders of the major political parties represented in the 50th parliament of the Bulgarian National Assembly. The leaders announce their plans for the new season, which should represent the political principles embraced by the respective parties. Metaphor is defined following George Lakoff’s definition as a cognitive mechanism of making sense of the world. Specific reference is made to his classification of political metaphors of the state as a family. Where metaphors fall outside the scope of the American taxonomy - as can be expected of the Bulgarian context, new categories are introduced based on the empirical material. Conclusions are sought about each speaker’s conceptual system and the nature of the political ideas presented by them.